FORMATION OF IDEOLOGY AND DEMOCRATIC THINKING - A. Negmatova,; Khamrakulova Gulzade Azimzhanovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
in this scientific article, the formation of a scientific worldview in the younger generation has been the focus of attention of advanced people of the nation at all times. In all the regimes experienced by mankind, educated, educated people of the era made significant contributions to the universal culture of World Science.